Crossing mucosal barriers for non-invasive protein delivery: a vitamin B12-mediated approach - Fowler, R.C. (2013)
Mucosal delivery of biotherapeutics as a non-invasive means of delivery could potentially be enhanced using nanoscale therapeutic carriers. However, nanoparticles do not readily cross the mucosal barriers, with the epithelium severely restricting their translocation into the systemic circulation. Translocation of nanocarriers across the mucosae may be improved by employing ligands capable of exploiting receptor-mediated cell uptake processes.